PHYSICS LEARNING DEVELOPMENT WITH APPLYING OUTDOOR INQUIRY APPROACH TO GROW STUDENT SCIENTIFIC WORK HABITS ON GRADE XI SENIOR HIGH SCHOOL - Riza Ayu Wardani; Zulhelmi Zulhelmi; M. Rahmad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
The purpose of this research to produce learning devices by applying an outdoor-inquiry approach to fostering scientific work habits on the rotational dynamic material and the equilibrium of a valid rigid objects. The benefits of this research are the product can be used as teaching materials teacher guides, add science insight , guide students in self-development and foster the habits of student scientific work. Tthe method research was a Research and Development (R & D). Method steps include potentials and problems, literature studies and information gathering, product design, validation, and proven design. Data collection was done through learning device validation sheet by 5 validators, consisting of 3 physics education lecturers and 2 physics teachers. The instrument of learning device validity developed consisted of RPP validation instrument, LKPD and understanding items. Validation is done by two stages, that is validation phase I and validation phase II. The result of learning device validation phase I get the average value 2,78 with high category. The result of learning device validation phase II obtained the average value 3,15 with high category.